Factors associated with perinatal and neonatal deaths in Sao Tome & Principe: a prospective cohort study - Vasconcelos, Alexandra; Sousa, Swasilanne; Bandeira, Nelson; Alves, Marta; Papoila, Ana Luísa; Pereira, Filomena; Machado, Maria Céu (Frontiers in Pediatrics, 2024)
Background Neonatal mortality reduction is a global goal, but its factors are seldom studied in most resource-constrained settings. This is the first study conducted to identify the factors affecting perinatal and neonatal deaths in Sao Tome & Principe (STP), the smallest Central Africa country. Methods Institution-based prospective cohort study conducted at Hospital Dr. Ayres Menezes. Maternal-neonate dyads enrolled were followed up after the 28th day of life (n = 194) for identification of neonatal death-outcome (n = 22) and alive-outcome groups (n = 172). Data were collected from pregnancy cards, hospital records and face-to-face interviews. After the 28th day of birth, a phone call was made to evaluate the newborn's health status. Crude odds ratios and corresponding 95% confidence intervals were obtained. A p value <0.05 was considered statistically significant. Results The mean gestational age of the death-outcome and alive-outcome groups was 36 (SD = 4.8) and 39 (SD = 1.4) weeks, respectively. Death-outcome group (n = 22) included sixteen stillbirths, four early and two late neonatal deaths. High-risk pregnancy score [cOR 2.91, 95% CI: 1.18–7.22], meconium-stained fluid [cOR 4.38, 95% CI: 1.74–10.98], prolonged rupture of membranes [cOR 4.84, 95% CI: 1.47–15.93], transfer from another unit [cOR 6.08, 95% CI:1.95–18.90], and instrumental vaginal delivery [cOR 8.90, 95% CI: 1.68–47.21], were factors significantly associated with deaths. The odds of experiencing death were higher for newborns with infectious risk, IUGR, resuscitation maneuvers, fetal distress at birth, birth asphyxia, and unit care admission. Female newborn [cOR 0.37, 95% CI: 0.14–1.00] and birth weight of more than 2,500 g [cOR 0.017, 95% CI: 0.002–0.162] were found to be protective factors. Conclusion Factors such as having a high-risk pregnancy score, meconium-stained amniotic fluid, prolonged rupture of membranes, being transferred from another unit, and an instrumental-assisted vaginal delivery increased 4– to 9–fold the risk of stillbirth and neonatal deaths. Thus, avoiding delays in prompt intrapartum care is a key strategy to implement in Sao Tome & Principe.